Developing a Python algorithm to calculate pressure changes during cement displacement in oilfield wells - Pap, József; Baracza, Mátyás Krisztián; Turzó, Zoltán Tibor (Multidiszciplinaris Tudomanyok, 2024)
Cementing is a crucial step when developing an oilfield well, which is usually done by pumping high-density slurry through the casing and then displacing it to the annular section. However, especially in deep structures, the whole process should be handled with increased care due to presence of excess hydrodynamic pressure. This may reach casing burst and collapse pressure limits, moreover formation fracture pressure limit in certain cases. This study introduces an algorithm, developed in Python, able to calculate dynamic pressure changes during cementing operations, and to alert when a critical pressure is reached at any point.